Qualidade da educação e políticas educacionais no período de 2003 a 2010: uma análise nos governos de Lula da Silva - Veiga, Robson Antônio dos Reis (2016)
This research is set in the context of the research line State, Policies and Management in Education, which integrates the Post-Graduate Program in Education of the Federal University of Uberlândia (UFU), linked to a project titled “Articulated Actions Plan Evaluation: a study in municipalities of Rio Grande do Norte, Pará and Minas Gerais, from 2007 to 2012”, developed by the Education Observatory (OBEDUC). It aims to investigate the issue concerning the quality in the sphere of educational policies orientated to basic education between 2003 and 2010. More specifically, it has the objective to analyze the conceptions of quality related to educational policies which were directed to basic education from 2003 to 2010, under Lula’s government. Bibliographical analysis was chosen as methodology with the purpose of understanding points about educational management, educational quality and educational policies to basic education in Brazil. It was also made the documentary analysis to check legal texts, plans, programs, projects, studies and other relevant publications for our object of study. The path taken in this research has demonstrated the prominence of quality as a theme within the ambit of the public policies introduced in Brazil since the 1990’s, when it happened an administrative restructuring of the Brazilian State, especially because of the management model adopted by Fernando Henrique Cardoso’s government (1995-2002). Its main brand in education is typical of the business world, and it is called Total Quality Management (TQM). In opposition to that conception of quality, several educators have been defending the social quality of education. More recently, during the educational policies proposed by Lula’s government, a set of actions, plans and programs was launched to improve the quality of education, such as the National Education Plan (PDE). In basic education, the Target Plan All for Education Commitment, the Index of Basic Educational Development (IDEB) and the Articulated Actions Plan (PAR) were established by means of Decree 6.094/2007. Results show that: a) ambiguously, Total Quality Management and social quality education permeated the discussion on the political actions in Lula’s Government (2003-2010); b) the discussion about quality occurred through the strategic planning anchored in Federal Constitution of 1988; c) the Target Plan aims to improve the quality of education by strengthening the cooperation between the federated entities; d) IDEB was established as a synonym of quality; e) PAR is a planning instrument by which federal government intends to make the cooperation stronger.